The influence of dynamic governance on public service innovation: Analysis of recruitment of officials of public organizations in local government - Waris, Irwan; Susanti, Ani; Haryono, Dandan (International Journal of Innovative Research and Scientific Studies, 2025)
Dynamic governance is considered an important approach to stimulate innovation in public services as well as the recruitment process of managers in the public sector. This study aims to investigate the impact of dynamic governance on public service innovation by raising the recruitment of public sector managers as a variable that functions as a reinforcer. The method used in this study is a quantitative approach, where data is collected and analyzed through surveys. A total of 340 participants were enrolled using a disproportionately random sampling technique, referring to the Krejcie and Morgan [1] tables, with an error tolerance of 0.05. The findings of this study indicate that dynamic governance consists of two elements that exert a positive and significant influence on public service innovation: dynamic capabilities and institutional culture. In addition, the results also show that the process of hiring managers in public organizations contributes positively and significantly to innovation in public services. Therefore, a dynamic governance approach is considered important to improve performance, resilience, and adaptation in local government. Furthermore, it also has the potential to increase the effectiveness of hiring managers in the public sector and facilitate better innovation in the future.